2022
DOI: 10.3390/plants11111430
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Integrative Omic Approaches for Understanding Rice Salt Response Mechanisms

Abstract: Soil salinity is one of the most serious environmental challenges, posing a growing threat to agriculture across the world. Soil salinity has a significant impact on rice growth, development, and production. Hence, improving rice varieties’ resistance to salt stress is a viable solution for meeting global food demand. Adaptation to salt stress is a multifaceted process that involves interacting physiological traits, biochemical or metabolic pathways, and molecular mechanisms. The integration of multi-omics app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 314 publications
0
11
0
Order By: Relevance
“…If plants suffer from inordinate amounts of salt, this will lead to various metabolic perturbations, cutback in water potential (ψw), disordered membrane potential, weaken photosynthesis and diminish nitrogen assimilation [26][27][28]. However, plants have evolved many adaptative mechanisms in response to the condition of high salinity, which involves interacting physiological traits, biochemical or metabolic pathways, and molecular mechanisms [29]. Among them, carotenoids are proved to respond to salt stress [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…If plants suffer from inordinate amounts of salt, this will lead to various metabolic perturbations, cutback in water potential (ψw), disordered membrane potential, weaken photosynthesis and diminish nitrogen assimilation [26][27][28]. However, plants have evolved many adaptative mechanisms in response to the condition of high salinity, which involves interacting physiological traits, biochemical or metabolic pathways, and molecular mechanisms [29]. Among them, carotenoids are proved to respond to salt stress [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Organic acids can form metal–ligand complexes (Tahjib-Ul-Arif et al 2021 ; Vega et al 2022 ) at the root surface or in the cytosol that prevent metal(loid)s from entering vital cellular pathways. Several studies have reported the synthesis and release of low molecular weight organic acids, such as acetic acid and succinate, by roots as an effective strategy for Cd tolerance in the accumulator genotype (Mnasri et al 2015 ; Ubeynarayana et al 2021 ). For example, low-level As increased the secretion of low molecular weight organic acids like citric, oxalic, and malic acid in the rhizosphere of mangroves (Mei et al 2021 ).…”
Section: Plant Responses and Adaptation To Metal(loid) Toxicitymentioning
confidence: 99%
“…Particularly, proteogenomics is useful for the identification of proteins by integrating genomic, transcriptomic and MS data of the same crop species and/or sample. Thus, the integrative proteogenomics approach has identified novel proteins and provided a hardcore knowledge of the genes’ regulatory expression and cell signalling for abiotic stress tolerance [ 253 ]. Proteogenomics has shed light on the mechanisms of plants’ response to abiotic stress and adaptation to changing the environment.…”
Section: Proteogenomics Lipidomics Ionomics and Interactomicsmentioning
confidence: 99%